A Short Textual Commentary on the Book of Revelation and the “New” Nestle - Elliott, J. K. 1943-2024 (2014)
This is an analysis of a representative selection of text-critical variants in the Book of Revelation. In particular the variants include those that concern the author’s language and style and those involving grammatical features. The attempted solutions offered are based on the principles of thoroughgoing eclectic criticism.
Keywords: Bibel; Nestle-Aland -- Novum Testamentum Graece -- thoroughgoing eclectic criticism -- Revelation -- homoioteleuton -- United Bible Societies -- Greek New Testament